Influence of dissipation on a low-voltage dc current in a long SNS junction: Сильно коррелированные системы и высокотемпературная сверхпроводимость - Kulinich, Sergey I.; Shekhter, Robert I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The dc current through a voltage-biased long transparent SNS junction in a dissipative regime is considered. The problem under certain conditions is mapped onto exactly solvable model of energy pumping into a quasiballistic 1D quantum ring driven by time-dependentmagnetic flux. A rich peak-like structure of the subgap current at low voltages is predicted. The maxima in the current correspond to resonant energy absorption for fractional values of the normalized bias voltage.